Synthesis and Structural Characterization of N-(2-Hydroxyphenyl)tetrachlorophthalimide - Li, Jian (Asian Journal of Chemistry, 2016)
N-(2-Hydroxyphenyl)tetrachlorophthalimide (C14H5NO3Cl4, Mr = 376.99) was synthesized and characterized by elemental analysis, 1H NMR spectra and single crystal X-ray diffraction. The crystal belongs to monoclinic, space group P21/c, with a = 12.2501(16), b = 14.3426(18), c = 20.092(3) Å, b = 55.038(2)º, V = 2893.0(6) Å3, Z = 8, Dc = 1.731 g/cm3, l = 0.71073 Å, μ(MoKa) = 0.828 mm-1, F(000) = 1504. The final refinement gave R = 0.0351, wR = 0.0847 for 5, 102 observed reflections with I > 2s(I). The asymmetric unit of the title compound contains two independent molecules. The dihedral angles between the phthalimide and 2-hydroxyphenyl groups are 64.6 (2)º and 64.5 (2)º, respectively, in two independent molecules of the asymmetric unit. The molecules of the crystal are connected, via the intermolecular O-H...O hydrogen bonds interactions, to form network.